Tracheostomy A Surgical Guide (Springer International Publishing, 2018)
Despite often taken as a simple procedure, techniques on tracheostomy have evolved considerably on the last few years. Consequently, new technical variations and indications for different purposes are being developed and proposed. The current book was prepared to serve as a comprehensive guide exclusively devoted to tracheostomy, discussing its most important details, variations and indications. Here the reader will find a broad discussion ranging since the most basic pre-clinical aspects until post-surgical procedures and complications. Great emphasis are placed in key topics such as the oncologic patient, variations of the technique, tracheostomy in the intensive care unit, among others. Additionally, some issues that are not commonly discussed in regular textbooks, like tracheostomy in child and in great obese, are also included. With a wealth of photos, illustrations and tables, Tracheostomy - A Surgical Guide provides the material necessary to support a safe and effective surgical intervention in different populations and surgical contexts, with the hope that it will result in improved care for patients who underwent tracheostomy.